MITOS KULTURAL DALAM OBJEK DESAIN: Analisis Terhadap Karakter Antropomorfis - Adi, Anggar Erdhina (Capture : Jurnal Seni Media Rekam, 2011)
Culture is always evolving and changing to follow the society development. The result alwaysleaves footstep in the form of value or artifacts. The character design in the past was amanifestation of the people culture as expression value in the form of artifacts, one of theforms is anthropomorphic characters. Meanwhile, in the modern era the realization comes inmany forms; for instance movies, comics, and novels with a variety of designs. This embodimentcannot be separated from the cultural values as a constituent. The object is understood asa truth because it becomes a cultural myth. This paper attempts to interpret the phenomenonof design objects in the form of character anthropomorphic as a design object.